Evaluation of energy loss in patients with severe primary valvular heart disease before cardiac valve intervention. (4th February 2022) - Pugliese, NR; Del Punta, L; Falcetta, G; Besola, L; De Biase, N; Mazzola, M; Giannini, C; Petronio, AS; Taddei, S; Masi, S; Colli, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Valvular heart disease (VHD) determines non-physiological, inefficient blood flow within the left ventricle, resulting in abnormal vortex formation and energy loss (EL). EL evaluation could provide valuable insights in addition to more common parameters of left ventricle systolic and diastolic dysfunction. Vector flow mapping (VFM) is a novel, non-invasive echocardiographic technique that measures EL through the study of intraventricular flow. Purpose. To assess EL throughout the whole cardiac cycle in patients with severe primary left-sided VHD before cardiac valve intervention. Methods. VFM is based on the continuity equation applied to colour Doppler and speckle tracking echocardiography, acquired from the apical long-axis view. VFM estimates blood flow velocity and vortex characteristics to quantify energy dissipation (i.e., EL) due to blood viscosity in a turbulent flow. EL was calculated frame by frame and averaged over three beats. Results. We enrolled 20 healthy controls (55 ± 19 years old, 65% male) and 73 patients (70 ± 17 years old, 59% male) with severe VHD before cardiac surgery: 30 with primary mitral regurgitation (MR), 8 with mitral stenosis (MS), 15 with aortic regurgitation (AR), 20 with aortic stenosis (AS). All patients had a left ventricle (LV) ejection fraction ≥50% and no wall motion abnormalities. We observed an increased number of vortexes in patients with VHD when compared to controls, especially in mid-diastole (p = 0.003). This is reflected in a significantly higher EL during the whole cardiac cycle in VHD patients than controls (p < 0.0001), with the highest values observed in MS and AR (post-hoc test: all p < 0.0.1; Figure 1 and Figure 2). The differences were driven by the diastolic EL (p < 0.0001), while the systolic EL values were similar between patients with VHD and controls (p = ns). Conclusions. In addition to standard baseline echocardiography, VFM can quantitatively evaluate the energy dissipation in different subsets of VHD. EL is not uniform during the cardiac cycle, as diastole seems significantly more affected than systole. The assessment of EL after valve intervention is ongoing. VFM could provide further insights into the pathophysiology of heart valve disease and help to evaluate the efficacy of the procedure (repair/replacement) performed.